Multiplex polymerase chain reaction to detect Salmonella serovars Indiana, Enteritidis, and Typhimurium in raw meat. Issue 5 (25th June 2019) - Xu, Jingxiao; Zhang, Ping; Zhuang, Linlin; Zhang, Di; Qi, Kezong; Dou, Xinhong; Wang, Chengming; Gong, Jiansen
Abstract: Salmonella ‐contaminated raw food is an important source of human food poisoning. Traditional methods for detecting Salmonella in meat involve many time‐consuming and laborious steps, preventing timely and effective control of the pathogen. In this study, a multiplex polymerase chain reaction (PCR) assay that targets serovar‐specific genes such as A7P63_0910 ( Salmonella Indiana), sdfI ( Salmonella Enteritidis), and STM4497 ( Salmonella Typhimurium) for three meat‐associated Salmonella serovars was established. This multiplex PCR has been validated by extensive testing on reference strains and clinical isolates belonging to different Salmonella serovars ( n = 348) and non‐ Salmonella bacteria ( n = 12). The detection limit is 100 CFU per reaction for bacterial culture, being equivalent to 10 pg per reaction for bacterial genomic DNA. Detection of Salmonella in raw meat samples by this multiplex PCR revealed that the prevalence of S . Indiana, S . Enteritidis, and S . Typhimurium is 7.7%, 5.7%, and 2.0%, respectively. The multiplex PCR established in this study can be used as a novel and convenient tool for simultaneous detection of three major meat‐associated Salmonella serovars, including the newly emerging and highly drug‐resistant S . Indiana. Practical applications: In this study, a multiplex polymerase chain reaction (PCR) assay that targets serovar‐specific genes such as A7P63_0910 ( Salmonella Indiana), sdfI ( Salmonella Enteritidis), and STM4497 ( Salmonella Typhimurium) for three meat‐associated Salmonella serovars was established. This multiplex PCR is suitable for the simultaneous detection and differentiation of three major meat‐associated Salmonella serovars, and has been validated by extensive testing of reference strains and clinical isolates. The multiplex PCR assay can provide rapid and specific screening for top three Salmonella serovars in meat samples.